Selection of organic materials potentially used to enhance bioremediation of acid mine drainage - Fitri Arum Sekarjannah; Irdika Mansur; Zaenal Abidin (Brawijaya University, 2021)
Acid mine drainage (AMD), produced when sulfide minerals are subjected to oxygen and water, is one of the major issues in mining industries. Without proper management, AMD's release to the environment would cause seriously prolonged environmental and health issues, such as increases soil acidity and reduces water quality due to extremely low pH, high sulphate concentration, and heavy metal solubility. AMD treatments are divided into two categories, i.e., active treatment, conducted by applying a chemical to the AMD to neutralize pH and precipitate heavy metals; and passive treatment, which relies on biological and biochemical processes. The active treatment may provide an immediate effect, but costly and yet sustainable; meanwhile, passive treatment takes time to establish and to generate an effect, but it is more economical, sustainable, and environmentally friendly. The wetland system is an example of passive treatment. Therefore, this review focuses on passive treatments, especially the selection of organic materials used in constructed AMD wetland treatment. Organic materials play a central role in the wetland system, i.e., to chelate metal ions, remove sulphate from the solution, increase pH, and growth media for microbes, especially sulphate reducing bacteria (SRB) and plants are grown in the system. Overall, organic materials determine the effectiveness of the wetland system to neutralize AMD passively and sustainably.